Coronavirus Disease 2019 (COVID-19): Emerging and Future Challenges in Toxicology Practice - M. Motawei Shimaa (Journal of Current Viruses and Treatment Methodologies, 2020)
This article reviews toxicology practice challenges during COVID‑19, including laboratory safety, chemical exposures, therapeutics, and public health messaging. It identifies research needs and operational adaptations to support preparedness for future events.